Hepatitis C virus testing, liver disease assessment and direct‐acting antiviral treatment uptake and outcomes in a service for people who are homeless in Sydney, Australia: The LiveRLife homelessness study. Issue 8 (2nd May 2019) - Bajis, Sahar; Grebely, Jason; Cooper, Lucy; Smith, Julie; Owen, Greg; Chudleigh, Alan; Hajarizadeh, Behzad; Martinello, Marianne; Adey, Sara; Read, Phillip; Gilliver, Rosemary; Applegate, Tanya; et al.
Abstract: People who are homeless have increased hepatitis C virus (HCV) infection risk, and are less likely to access primary healthcare. We aimed to evaluate HCV RNA prevalence, liver disease burden, linkage to care and treatment uptake and outcomes among people attending a homelessness service in Sydney. Participants were enrolled in an observational cohort study with recruitment at a homelessness service over eight liver health campaign days. Finger‐stick whole‐blood samples for Xpert® HCV Viral Load and venepuncture blood samples were collected. Participants completed a self‐administered survey and received transient elastography and clinical assessment by a general practitioner or nurse. Clinical follow‐up was recommended 2‐12 weeks after enrolment. For participants initiating direct‐acting antiviral (DAA) therapy, medical records were audited retrospectively and treatment outcome data were collected. Among 202 participants (mean age, 48 years), 82% were male (n = 165), 39% (n = 78) reported ever injecting drugs, of whom 63% (n = 49) injected in the previous month. Overall, 23% (n = 47) had detectable HCV RNA and 6% (n=12) had cirrhosis. HCV RNA prevalence among participants with either injecting or incarceration history was 35% (37/105), compared to 4% (3/73) among participants without these risk factors. Among those with detectable HCV RNA, 23 (49%) commenced therapy, of whom 65% (n = 15) achieved sustained virological response, while the remainder had no available treatment outcome. No participant had documented virological failure. HCV DAA treatment uptake among people attending a homelessness service was encouraging, but innovative models of HCV care are required to improve linkage to care and treatment uptake among this highly marginalized population.